Renin‐Angiotensin‐Aldosterone System and Hypothalamic‐Pituitary‐Adrenal Axis in Hospitalized Newborn Foals. (11th February 2013) - Dembek, K.A.; Onasch, K.; Hurcombe, S.D.A.; MacGillivray, K.C.; Slovis, N.M.; Barr, B.S.; Reed, S.M.; Toribio, R.E.
<x xml:space="preserve">Abstract</x> Background The renin‐angiotensin‐aldosterone system (RAAS) and hypothalamic‐pituitary‐adrenal axis (HPAA) and their interactions during illness and hypoperfusion are important to maintain organ function. HPAA dysfunction and relative adrenal insufficiency (RAI) are common in septic foals. Information is lacking on the RAAS and mineralocorticoid response in the context of RAI in newborn sick foals. Objectives/Hypothesis To investigate the RAAS, as well as HPAA factors that interact with the RAAS, in hospitalized foals, and to determine their association with clinical findings. We hypothesized that critical illness in newborn foals results in RAAS activation, and that inappropriately low aldosterone concentrations are part of the RAI syndrome of critically ill foals. Animals A total of 167 foals ≤3 days of age: 133 hospitalized (74 septic, 59 sick nonseptic) and 34 healthy foals. Methods Prospective, multicenter, cross‐sectional study. Blood samples were collected on admission. Plasma renin activity (PRA) and angiotensin‐II (ANG‐II), aldosterone, ACTH, and cortisol concentrations were measured in all foals. Results ANG‐II, aldosterone, ACTH, and cortisol concentrations as well as ACTH/aldosterone and ACTH/cortisol ratios were higher in septic foals compared with healthy foals (P < .05). No difference in PRA between groups was found. High serum potassium and low serum chloride concentrations were associated with hyperaldosteronemia in septic foals. Conclusions and Clinical Importance RAAS activation in critically ill foals is characterized by increased ANG‐II and aldosterone concentrations. Inappropriately low cortisol and aldosterone concentrations defined as high ACTH/cortisol and ACTH/aldosterone ratios in septic foals suggest that RAI is not restricted to the zona fasciculata in critically ill newborn foals.